Penerapan Model Pembelajaran Student Teams Achievement Division (STAD) untuk Meningkatkan Keterampilan Reading Comprehension Mahasiswa - Yusniarti Runggo; Hendriyani Hendriyani (Jurnal Kreatif Online, 2023)
Reading comprehension skills in English are needed of them by using a learning model, namely Student Teams Achievement Division (STAD). The purpose of the study was to improve reading comprehension skills in English. This study used a classroom action research design. The learning materials were readings related to agriculture and language structure. The results showed that the STAD model effectively improved reading comprehension skills in English. The implementation of learning in the first and second cycles showed an increase in student learning achievement. There were 14 (70%) students who succeeded, and 6 (30%) failed. Furthermore, the success increased to 20 (100%) students in the second cycle. The conclusion is the STAD type learning model can improve students' comprehension ability in reading English and increase students' role in active learning.